The Effect of Different levels and kinds of Cytokinins on Buds proliferation of Iraqian Date Palm Cultiver (Barhi) In vitro - Al-Khalisi, A. A. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study was conducted to determined the action of several levels of cytokinis (N6-benzyladenine (BA),  6-furfurylaminopurine (kinetin), N6-(âˆ†-isopentyladenine) (2,ip) on buds proliferation of Phoenix dactylifera L..3 ml explants of the heart of 3 years old offshoot were cultured on Murashige and Skoog medium (1962) containing 3 mg/L activated charcoal, 10 mg/L Naphthalene acetic acid  proposed by (1) as a control. Other explants were cultured on this medium supplemented with 0.1, 0.5, 1 mg/L BA. 0.1, 0.5, 1, 2, 3, 4 mg/L Kinetin. 0.1, 0.5, 1 mg/L 2,ip. Best number of buds proliferated has occurred on control medium containing 3 mg/L. 2ip.